Development and management of forest plantations a guidebook. - Philippines. Ecosystems Research and Development Bureau (College, Laguna Department of Environment and Natural Resources, ERDB, 1998)
A comprehensive guidebook for forest development and management. Topics included are seed technology, nursery establishment and management, and plantation establishment and management.
Keywords: Tree farms -- Management -- Philippines -- Handbooks, manuals, etc